The impact of the COVID-19 pandemic on the trend of prescribing long-acting injections of paliperidone and risperidone in Central Serbia - Stojkovic, Milena; Sekulic, Marija; Jovanovic, Mirjana; Kocovic, Aleksandar; Djokovic, Danijela; Minic, Natasa; Djordjic, Milan; Joksimovic, Stefan; Sorak, Marija; Stojanovic, Bojan; Sretenovic, Snezana; Cvetkovic, Aleksandra; et al. (Frontiers in Psychiatry, 2023)
Since the end of 2019, the global spread of COVID-19 has represented a historic event that changed our way of treating patients globally. The use of long-acting injections (LAI) antipsychotics was emphasized. Our goal was to investigate the impact of COVID-19 on the frequency of prescribing LAI and compare it with a period before. All patients (198) who started LAI-risperidone or LAI-paliperidone for the period 2017–2022, in Kragujevac, the city in Central Serbia, were considered. The frequency of prescribing LAI before and during COVID-19 and the total number of prescribed LAI per year were compared. Separately, the frequency of prescribing LAI-R and the frequency of prescribing LAI-P were compared. The significant (p < 0,05) increase in the use of LAI risperidone and paliperidone was in 2020 and 2021 [per year 2017(3), 2018(6), 2019(26), 2020(75), 2021(55), and 2022(33)]. The significant (p < 0,05) increase in monthly and quarterly preparations of LAI paliperidone was in 2020 and 2021 relative to the years before the pandemic. As the pandemic weakened, the inclusion of LAI paliperidone therapy weakened during 2022. A significant increase in usage of LAI risperidone was in 2022, and in 2020 and 2021 was as it was in the period 2017–2019. During COVID-19, especially in years when COVID-19 restriction measures were stricter, there was a significant change in the application method of antipsychotic therapy in favor of LAI. Regardless of the increase in treatment costs, patients’ interests and protection were prioritized in the treatment process.